Comparative waste management options for rigid polyurethane foam waste in Thailand. (20th September 2018) - Tantisattayakul, Thanapol; Kanchanapiya, Premrudee; Methacanon, Pawadee
Abstract: This research assesses the appropriate options for managing rigid polyurethane waste (RPUW) remaining from refrigerator/freezer dismantling in Thailand by analyzing the impacts on environment, energy and economic aspects. There are four options for RPUW management: option 1 – landfill; option 2 – incineration; option 3 – hydrolysis + landfill; and option 4 – production of lightweight concrete (LWC) mixed with RPUW (LWC-RPUW). From environmental and energy perspectives using Life cycle assessment (LCA) by Simapro software, the results showed that option 4 had the lowest human toxicity, followed by option 3, option 1 and option 2, respectively. On the other hand, option 1 had the lowest climate change and fossil depletion impacts, followed by option 2, option 3 and option 4, respectively. However, without considering energy consumption during the use phase of LWC as wall material in building, option 4 has the least energy and environmental impact. Regarding economic impact, option 4 is the only one option that can make a profit, and its net present value (NPV) is positive. In other words, it is worth refrigerator recyclers investing in a LWC-RPUW production plant. Option 4 is feasible to perform practically without subsidizing from any organization, while the other options are costly to carry out. To promote option 4, which is more appropriate considering all three kinds of impact studied here, it will be necessary to improve option 4 in terms of the insulation properties of the LWC-RPUW products to reduce the environmental impact from energy consumption during the product use phase.